Fullerenes (C60) versus heteroazafullerenes (C59N); a photophysical comparison of their monoadducts and hexaadducts - Guldi, Dirk Michael; Hirsch, Andreas; Hauke, Frank (Research on Chemical Intermediates, 2002)
The singlet and triplet excited state properties of a series of fullerene derivatives (C) are compared to those of the corresponding heteroazafullerenes derivatives (CN) by employing a variety of steady-state and time-resolved photophysical assays. The most far-reaching results infer that the CN (2, 5) analogous of C (1, 4) are characterized by shorter singlet lifetimes (1.01/0.57 ns versus 1.80/1.75 ns) and weaker fluorescence quantum yields (1.6 × 10/2.1 × 10 versus 6.0 × 10/1.09 × 10). This general conclusion applies for the monoadduct series (1, 2) and also for the highly functionalized hexaadducts (4, 5). Similarly, higher singlet energies (1.89 eV (4) versus 1.79 eV (1)) come together with higher fluorescence quantum yields for the hexaadducts than for the monoadducts.